1996
DOI: 10.1007/bf01253958
|View full text |Cite
|
Sign up to set email alerts
|

Colony composition and queen behavior in polygynous colonies of the oriental ponerine antOdontomachus rixosus (Hymenoptera Formicidae)

Abstract: Colony composition and behavior of queens in the ponerine ant Odontomachus rixosus were investigated in Bogor (West Java) and Ulu Gombak (Penisular Malaysia). The colonies had multiple dealate queens, with a maximum of 82 queens per colony. Majority of queens (92.4%) were inseminated and laid eggs, however, the degree of ovarian development slightly varied among individual queens. Queen behavior was observed for one colony in laboratory. Reproductive condition of individual queens was related with behavioral p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0
2

Year Published

1999
1999
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 24 publications
2
12
0
2
Order By: Relevance
“…Our study confirms previous observations on social structure in Odontomachus ants, which report the occurrence of multiple queens within colonies (Ledoux, 1952;Colombel, 1972;Peeters, 1987;Medeiros et al, 1992;Ito et al, 1996). So far we are not certain whether polygyny in this species results from groups of cofounding queens (pleometrosis) or from adoption of newly mated queens by established colonies (secondary polygyny).…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Our study confirms previous observations on social structure in Odontomachus ants, which report the occurrence of multiple queens within colonies (Ledoux, 1952;Colombel, 1972;Peeters, 1987;Medeiros et al, 1992;Ito et al, 1996). So far we are not certain whether polygyny in this species results from groups of cofounding queens (pleometrosis) or from adoption of newly mated queens by established colonies (secondary polygyny).…”
Section: Discussionsupporting
confidence: 72%
“…Indeed Colombel (1972) reported that small colonies of O. troglodytes were always monogynous whereas large colonies (*250 workers) were polygynous due to adoption of newly mated queens by mature colonies. Although Ito et al (1996) found no correlation between the number of queens and workers in colonies of O. rixosus, the fact that new colonies are always founded independently by solitary queens and that numerous queens are found in mature colonies indicate that functional polygyny in this species results from queen adoption. In the case of O. rixosus whose colonies may contain [70 inseminated queens, lack of correlation between queen and worker numbers may stem from recent addition of young queens that might not have yet produced workers, or that might have left the colony with workers to found a new one by budding (see Peeters and Ito, 2001).…”
Section: Discussionmentioning
confidence: 57%
“…Winged queens have been reported in all species studied (e.g. Ito et al, 1996) except O. coquereli from Madagascar where only wingless reproductives have been found (Brown, 1976;Wheeler, 1910). Mated Odontomachus workers have never been found, although they can lay unfertilized eggs (van Walsum et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to primary polygyny, secondary polygyny maintains the reproductive function of all queens. Nevertheless, fecundity often varies among queens in polygynous species (Ross, 1988;Stille et al, 1991;Bourke and Franks, 1995;Ito et al, 1996). In extreme cases a single mated female lays eggs (functional monogyny) while others are sterile (Heinze and Smith, 1990;Ito, 1993).…”
Section: Introductionmentioning
confidence: 99%